Value chain analysis of Garlic in LiboKemkem District: In the era of COVID-19, South Gondar Zone Amhara Region, Ethiopia - Gedefaw Kindu Wubet (Cogent Business & Management, 2022)
Garlic is the main bulb crop produced in Libokemkem District, but this crop's value chain status and particular actors were not studied. Thus, the study aimed to assess the Garlic value chain in Libokemkem District, Ethiopia. Four hundred Garlic producers are selected through multistage random sampling techniques. Descriptive, inferential statistics were employed. Feasible General Least Square Model was used to analyze factors for Garlic market supply. According to survey results, three groups of actors are identified. 92.4% of Garlic value chain activities are undertaken by main actors, who constitute 89.6% of the total actors in the entire value chain. Wholesalers governed the chain; they have a 31.2% share of the complete Garlic supplied to the market. During COVID 19 Pandemic, the demand for Garlic products rose; surprisingly, its price also increased because it was considered to treat COVID 19. Quantity of Garlic produced; land allocated, lagged price, market information, experience, and oxen were the significant covariates affecting Garlic market supply positively. Amount of credit and gender were significant covariates that negatively affected Garlic's market supply. Among the many constraints that negatively affect the Garlic value chain are the absence of improved seed confirmed by 95.4% of farmers, high cost of input by 78% of farmers, diseases and pests approved by 81.5% of farmers, and lack of price setting policy framework. The policymakers and practitioners should pay attention to improved Garlic seed conditions, problems, and competitive marketing strategy to ensure sustainable value chain development and balance the demand and supply.
Keywords: 650; actors; FGLS model; Garlic; Libokemkem District; value chain analysis; value chain map